Architectural Order in St. Petersburg Interiors - Blinova, Elena K. (Actual Problems of Theory and History of Art, 2015)
Order as an architectural system was developed in the interiors of St. Petersburg buildings and construction its forms and compositions being carried out profoundly and consistently during the three centuries of the city’s history. There are about four thousand order interiors in St. Petersburg. Fixed in our memory, the order creates perceptual skills, and provides a feeling of an ensemble of images as well as a sense of an exterior and interior continuity. In the interiors of St. Petersburg the order overcomes stylistic polyphony, and succeeds antiquity in all spheres of compositional development. Order compositions — we might call them “an interior order” — are important decorative elements of interiors of various types and function. The entire thesaurus of the order system, and different types of the latter have been applied in the St. Petersburg interiors; proportional system and proportions are changed depending upon peculiarities and size of architectural space. Retaining all compositional principles of the order system in a new environment, architects preserve general image while changing structure, plans, materials, etc. They conduct an in-depth analysis of the “alien language”, and by means of developing new orders they create contemporaneous artistic images, thus forming a new consciousness.